Building Men's Grooming Customer Loyalty: The Influence Of Customer Experience And Customer Value On Beauty Clinics In The City Of Medan - Irmayanti Nasution; Dian Natari; Rade Juliman Lumbantoruan; Syafrizal Helmi Situmorang (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2024)
Lifestylei changesi havei madei bodyi carei ai basici necessityi fori bothi womeni andi men.i Ati thisi timei thei needi fori beautyi carei fori meni calledi mens'groomingi isi noti inferiori toi women.i Researchi objectivesi regardingi buildingi customeri experiencei andi customeri valuei fori malei consumeri loyaltyi ati beautyi clinicsi ini Medani City.i Thisi researchi methodi isi associativei research.i Thei samplei ini thisi studyi wasi takeni usingi ani accidentali samplingi technique.i Ini thisi study,i thei samplei sizei wasi 90i malei customersi ati 3i beautyi clinics,i namelyi Wbeautyi Skincare,i Natashai Skincare,i andi Dr.i Geetai Aestheticsi usingi ai questionnaire.i Thei datai wasi analyzedi withi SPSSi 25.i Thei resultsi showedi thati customeri experiencei hasi ai significanti positivei effecti oni customeri loyalty,i whichi meansi thati ifi thei goodi experiencei thati consumersi havei increases,i customeri loyaltyi willi alsoi increase.i Iti cani bei concludedi thati H0i isi rejectedi andi Hai isi accepted.i Customeri Valuei hasi ai significanti positivei effecti oni customeri loyalty,i whichi meansi thati ifi consumeri assessmenti ofi thei brandi increases,i consumeri loyaltyi willi alsoi increase.i Iti cani bei concludedi thati H0i isi rejectedi andi Hai isi accepted.i Together,i customeri experiencei andi customeri valuei havei ai significanti positivei effecti oni customeri loyalty,i whichi meansi thati ifi consumersi havei ai goodi experiencei andi highi assessment,i consumeri loyaltyi willi increase.i Iti cani bei concludedi thati H0i isi rejectedi andi Hai isi accepted.